Effect of Hydrolyzed Fucoidan from The Brown Seaweed Sargassum Binderi Sonder Towards Human Breast Cancer T47d Cell Lines - Sinurat, Ellya; Saepudin, Endang; Qosthalani, Fildzah Alfita (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
Fucoidan, a sulfated heteropolysaccharide, consists of L-fucose and sulfate ester groups as the main component. Over the past three decades, fucoidan structures and bioactivities have been widely studied. The chemical components (fucose, galactose, small monosaccharides and also the sulfate) and the molecular weights of fucoidans from different brown seaweed species produce different characteristics and structures of fucoidan. The activity of fucoidan against cancer cells has been reported to be affected strongly by their sulfate content and molecular weight. Low-molecular-weight fucoidans tend to have higher solubility and easily penetrate into cancer cells. The objective of this study was to investigate the effect of hydrolyzed of fucoidan on its anti cancer activity againts the breast cancer T47D cells. In this study, the fucoidan from the brown seaweed Sargassum binderi Sonder was extracted using 0.1 N HCl and was depolymerized by acid hydrolysis at various times and concentrations. Result showed that fucoidan hydrolyzed with 1 M trifluoroacetic acid (TFA) for 1.5 hours reached the maximum depolymerization process and resulted in the decrement of molecular weight from 785.12 kDa to 5.79 kDa as well as sulfate content from 18.63% to 8.69%. The IC50 values ofÂ  fucoidan and low molecular weight fucoidan against the breast cancer T47D cells were 60.03 mg/mL and 182.34 mg/ respectively. This result indicated that the sulfate content of fucoidan probably affected its anticancer bioactivities.Â